2015
DOI: 10.7195/ri14.v13i2.788
|View full text |Cite
|
Sign up to set email alerts
|

Uso de las redes sociales como elemento formativo en el aula: Análisis de la motivación del alumnado universitario

Abstract: This study analyzes the perception of university students on motivation toward learning generated by the use of social networks as a methodological strategy. 187 students in four subjects have participated. In subjects in group A social networks were used as critical to the development of student activities, whereas in group B the use of these tools has not been carried out. The research methodology has been mixed, using both a quantitative analysis (descriptive and inferential) and qualitative (interviews). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
1
1
0
4
Order By: Relevance
“…Furthermore, our findings showed that the methods used in the classroom were compatible with the use of ICTs, coinciding with the objectives of the university framed within the EHEA [30][31][32]. According to the previous literature [33][34][35][36][37], university students show a positive perception towards the use of active methods and the introduction of ICTs in the classroom as well as towards the management and organization of office hours, considering them motivating and that they stimulate participation in the classroom.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Furthermore, our findings showed that the methods used in the classroom were compatible with the use of ICTs, coinciding with the objectives of the university framed within the EHEA [30][31][32]. According to the previous literature [33][34][35][36][37], university students show a positive perception towards the use of active methods and the introduction of ICTs in the classroom as well as towards the management and organization of office hours, considering them motivating and that they stimulate participation in the classroom.…”
Section: Discussionsupporting
confidence: 68%
“…Within this line, we can state that these methods do not just benefit collaborative learning and improve academic achievement, but they also increase students' motivation regarding curricular content in higher education [35][36][37]. This study shares an innovative method carried out in two courses of significant difficulty for students with the objective of helping them with the theoretical and practical comprehension of the subject, keeping students motivated and participating in class and aiming to provide them with competencies that are useful for their professional futures.…”
Section: Discussionmentioning
confidence: 99%
“…Cada vez más se constata el uso de YouTube para buscar información, acceder a conceptos básicos o publicar producciones y contenidos generados por estudiantes y docentes (Al-Rahmi, Alias, Othman, Mari y Tur, 2018;Chenail, 2013;Moghavvemi, Sulaiman, Jaafar y Kasem, 2018;Zhu et al, 2018). Por su parte, Facebook se utiliza para intercambiar y analizar información de distintas temáticas (Castro y González-Palta, 2016;Hortigüela y Pérez, 2015;Iglesias y González, 2014;Serrat, 2015;Túñez y Sixto, 2012). Twitter es usado para impulsar y evaluar procesos de aprendizaje colaborativo, mediante la búsqueda de fuentes de información (García, Trigueros y Rivera, 2015), así como para compartir materiales y suscitar discusiones (Chawinga, 2017).…”
Section: Dimensión Aprendizaje (A)unclassified
“…En esta línea, tal y como apuntaban Hortigüela y Pérez (2015), asumiendo la riqueza metodológica que otorga el hecho de compartir experiencias, ideas y proyectos con otros miembros de la comunidad educativa, la utilización de las redes sociales en un entorno presencial favorecía la creación de vínculos formativos que inciden en el tratamiento de una temática determinada. Para estos autores, la motivación era crucial, demostrando que lo importante no era el nivel que los alumnos adquieren en dicho uso, sino el modo en el que el docente orienta el proceso para obtener un mayor aprendizaje (Hortigüela & Pérez, 2015).…”
Section: Introductionunclassified